Heterozygous females from a rat model for creatine transporter deficiency reveal altered behavioral response to stressors, normal body weight and slight metabolic changes - Duran-Trio, Lara; Lanzillo, Marc; Simicic, Dunja; Roux-Petronelli, Clothilde; Bruce, Stephen J.; Sandi, Carmen; Cudalbu, Cristina; Braissant, Olivier (Frontiers in Neuroscience, 2025)
Creatine (Cr) is an organic acid essential for recycling ATP, important in tissues with high energy demand such as muscle or brain. Cr is synthesized in a 2-step pathway by the enzymes AGAT and GAMT, and transported by SLC6A8 (also called CrT). Cerebral Cr deficiency syndromes (CCDS), due to AGAT, GAMT or CrT deficiencies, are metabolic diseases characterized by brain Cr deficiency, causing a range of clinical features such as severe neurodevelopmental delays and intellectual disability, behavioral disturbances, motor dysfunction and epilepsy. Among CCDS, the X-linked CrT deficiency (CTD) is the most prevalent with no efficient treatment so far. Increasing number of human and animal studies contributes to the understanding of CTD pathology, its diagnosis and treatment, and the roles of Cr and CrT. However, most of them are focused in males and little is known about female carriers and how CrT deficiency affect them. In order to increase knowledge in female sex and roughly explore the relationship with SLC6A8 gene dosage, we present the first characterization of females' Slc6a8Y389C rat model of CTD using both heterozygous and homozygous females. Brain Cr deficiency was found in all homozygous females, while heterozygous ones showed broad variability in brain Cr levels. Elevated and slightly elevated urinary Cr/Crn ratio were present in homozygous and heterozygous females, respectively. Reduced body weight, muscular mass and locomotor activity were hallmarks of homozygous, but not heterozygous, females. However, in contrast to Slc6a8Y389C KI males, spontaneous alternation and grooming behaviors were not affected in any type of Slc6a8Y389C mutant female rats. Interestingly, both Slc6a8Y389C mutant female rats exhibited behavioral abnormalities such as increased prevalence of altered behavioral response to handling, being more frequent in homozygous female rats. Moreover, heterozygous females presented increased anxiety-like behavior to novelty in Open Field Novel Object test and altered behavioral response with increased locomotor activity in response to light as stressor in the Light Dark Box test. These results are coherent with the limited data from CTD human female carriers, validating the Slc6a8Y389C rat females as a promising tool to better understand CTD in female sex. They also provide new insights about CTD pathology, revealing sex and zygotic phenotypic differences, highlighting the importance of including females in the study of CTD.